Advances in Intelligent Information Hiding and Multimedia Signal Processing Proceedings of the Thirteenth International Conference on Intelligent Information Hiding and Multimedia Signal Processing, August, 12-15, 2017, Matsue, Shimane, Japan, Part II - Pan, Jeng-Shyang.; Tsai, Pei-Wei.; Watada, Junzo; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume includes papers presented at IIH-MSP 2017, the 13th International Conference on Intelligent Information Hiding and Multimedia Signal Processing, held from 12 to 15 August 2017 in Matsue, Shimane, Japan. The conference addresses topics ranging from information hiding and security, and multimedia signal processing and networking, to bio-inspired multimedia technologies and systems. This volume of Smart Innovation, Systems and Technologies focuses on subjects related to massive image/video compression and transmission for emerging networks, advances in speech and language processing, information hiding and signal processing for audio and speech signals, intelligent distribution systems and applications, recent advances in security and privacy for multimodal network environments, multimedia signal processing, and machine learning. Updated with the latest research outcomes and findings, the papers presented appeal to researchers and students who are interested in the corresponding fields.
Extraction of EEG Components Based on Time-frequency Blind Source Separation -- An Algorithm for Asymmetric Clipping Detection based on Parameter Optimization -- Automatic Facial Age Estimate based on Convolution Neural Network -- Fast Intra Mode Decision Algorithm for 3D-HEVC Transcoding XiuJun -- Implementation of a Drone-based Video Streamer -- Dialog-based Interactive Movie Recommendation: Comparison of Dialog Strategies -- A Study on 2D Photo-Realistic Facial Animation Generation Using 3D Facial Feature Points and Deep Neural Networks -- Towards an Interrogation Speech Manipulation Detection Method using Speech Fingerprinting -- An Automatic Detection Method for Morse Signal based on Machine Learning -- Capacity Reduction of Distribution Transformer by Harmonic Effect -- Building of a Practical Monitoring System for the Small Wind Turbine -- A Survey of Secret Sharing Schemes based on Latin Squares -- A Pre-assigned Key Management Scheme for Heterogeneous Wireless Sensor Networks -- A ProtocolVulnerability Analysis Method Based on Logical Attack Graph -- A New Approach of Shape Recognition with Ane Invariance based on HSC.
Keywords: Computational intelligence; Artificial intelligence; Signal processing; Multimedia systems; Computational Intelligence; Artificial Intelligence; Signal, Speech and Image Processing; Multimedia Information Systems